Paving the way for systemic phenomenological psychiatry - the forgotten heritage of Wolfgang Blankenburg - Thoma, Samuel; Konrad, Michael; Fellin, Lisa C.; Galbusera, Laura (Frontiers in Psychiatry, 2022)
Phenomenological psychopathology focuses on the first-person experience of mental disorders. Although it is in principle descriptive, it also entails an explanatory dimension: single psychological symptoms are conceived as genetically arising from a holistic structure of personal experience, i.e. the patient’s being-in-the-world – and of its dynamic unfolding over time. Yet both classical and current phenomenological approaches tend to identify the essential disorder or “trouble générateur” (Minkowski) of mental illness within the individual, thereby neglecting the relevance of the social context not only for the emergence of symptoms but also for their treatment. The work of Wolfgang Blankenburg on schizophrenia represents a noteworthy approach to overcome this individualistic tendency. He introduced the concept of “loss of common sense” as the structural core of schizophrenic experience and being-in-the-world and he considered the social and most importantly familial context for the emergence of schizophrenic experience. By accounting not only for personal experience but also for interactional structures of families and social milieus in which experience is embedded, Blankenburg thereby offered ways to combine phenomenological and systemic explanations of mental disorders. Beside his most renown work on “the loss of common sense”, in this paper we also present his family studies of young persons with schizophrenia, which have so far received little if no attention. We thus discuss the different ways in which Blankenburg expanded the phenomenological approach into a more systemic and social direction. We then link Blankenburg’s work it with current systemic explanatory models to schizophrenia and explore the clinical and scientific implications of this link. Finally, we call for further research on the synergy effects between the two.